Christians against Christianity: how right-wing Evangelicals are destroying our nation and our faith - Hendricks, Obery Mack (Beacon Press, 2021)
"Shows the many ways today's right-wing evangelical Christianity is the antithesis of the message of Jesus, and how their dangerous and false of the Christian faith is destroying both the faith and American society"--